2011
DOI: 10.1038/nphys2092
|View full text |Cite
|
Sign up to set email alerts
|

Strong back-action of a linear circuit on a single electronic quantum channel

Abstract: The question of which laws govern electricity in mesoscopic circuits is a fundamental matter that also has direct implications for the quantum engineering of nanoelectronic devices. When a quantum-coherent conductor is inserted into a circuit, its transport properties are modified; in particular, its conductance is reduced because of the circuit back-action. This phenomenon, known as environmental Coulomb blockade, results from the granularity of charge transfers across the coherent conductor 1 . Although exte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(79 citation statements)
references
References 31 publications
(68 reference statements)
7
72
0
Order By: Relevance
“…At zerofrequency or for an energy-independent transmission amplitude, αβ S αβ (ω) vanishes. This sum is non-zero only when t(ε) acquires an energy dependence, as it is the case for example when the system is coupled to an electromagnetic environment 54 .…”
Section: B Results and Discussionmentioning
confidence: 99%
“…At zerofrequency or for an energy-independent transmission amplitude, αβ S αβ (ω) vanishes. This sum is non-zero only when t(ε) acquires an energy dependence, as it is the case for example when the system is coupled to an electromagnetic environment 54 .…”
Section: B Results and Discussionmentioning
confidence: 99%
“…1) in an unified way. Indeed, our results apply to: (i) A one-channel conductor coupled to a measurement circuit the resistance of which equals the quantum of resistance, an experimental configuration which is realizable with a quantum point contact; 22 (ii) a constriction in a two-dimensional electron gas in the fractional quantum Hall regime with a specific filling factor; and (iii) a quantum dot coupled to two reservoirs.…”
Section: Introductionmentioning
confidence: 89%
“…For example, in Ref. 24 it was reported that Z e (ω) ≈ R ∼ R K up to frequencies of the order ω ∼ 1 GHz, C ≈ 2 fF, which translates to E C ≈ 10 −4 eV, and T = 25 mK, so that E C , ω k B T . These numbers give g ∼ 1 and lead for a large value of the induced voltage, eV ≈ 0.…”
Section: B Ohmic Environmentmentioning
confidence: 99%
“…Finally, let us give some realistic estimates for the induced voltage based on numbers utilized for observing the DCB in normal (ultra-small) tunnel junctions 24,25 and Josephson (superconducting) junctions 26 . Since we are considering ferromagnetic metals, we believe that such estimates are also appropriate for ultra-small MTJs, such as those investigated here.…”
Section: B Ohmic Environmentmentioning
confidence: 99%